MAIN METHODOLOGICAL PRINCIPLES PERTAINING TO STUDY OF THE BELARUSSIAN NATIONAL MOVEMENT IN PERIOD OF WORLD WAR I IN «BELARUS HISTORY» COURSE - N. V. Schavlinsky (Наука и техника)
The paper shows an actual importance  and proves the necessity to study the Belarussian national movement during World War I (1914–1918) in “Belarus History” course. Main methodological principles that allow to achieve the required goals and tasks in the process of problem consideration are revealed in the paper.